2011
DOI: 10.1590/s1516-31802011000600009
|View full text |Cite
|
Sign up to set email alerts
|

Primary epidermoid carcinoma of the breast presenting as a breast abscess and sepsis

Abstract: Primary epidermoid carcinoma of the breast presenting as a breast abscess and sepsisresUMo CONTEXTO: O carcinoma de células escamosas da mama é um câncer extremamente raro, representando cerca de 0,04% dos tumores malignos da mama. Até o momento, apenas um número limitado de casos da doença foi relatado, a maioria se apresentando clinicamente como um carcinoma de mama usual. RELATO DE CASO: Paciente feminina de 39 anos de idade se apresentando com grande abscesso de mama e sinais de sepse. Após debridamento ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 23 publications
0
19
0
3
Order By: Relevance
“…Some authors have noted only rare involvement of the lymph nodes [ 1 – 4 ]. There are no typical findings on the mammogram,ultrasound may show a complicated cyst or an inflammatory process [ 5 ]. Our patient was 43 year old, without significant medical history, she had an infected mass of 9cm associated with ipsilateral axillary lymphadenopathy, without typical findings on the mammogram.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have noted only rare involvement of the lymph nodes [ 1 – 4 ]. There are no typical findings on the mammogram,ultrasound may show a complicated cyst or an inflammatory process [ 5 ]. Our patient was 43 year old, without significant medical history, she had an infected mass of 9cm associated with ipsilateral axillary lymphadenopathy, without typical findings on the mammogram.…”
Section: Discussionmentioning
confidence: 99%
“…Tanıda mamografiye özgü bir bulgu yokken, USG'de kompleks kistik bileşenlerden oluşan solid hipoekojenik kitle görüntü-sünün tanı için daha yararlı olabileceği bildirilmiştir [3]. Oldukça nadir olarak meme apsesi şeklinde prezente olur [5,6]. Bizim olgumuzda da meme apsesi semptom ve bulguları üzerine istenilen USG'de yoğun içerikli kistik lezyon izlenmiştir.…”
Section: Discussionunclassified
“…Diğer meme tümör-lerinin aksine aksiller metastaz %10-30 arasında görülmektedir [3]. Ancak tedavide kemoterapinin (KT) rolü ve etkinliği konusunda kısıtlı bilgi olduğun-dan aksiller diseksiyon mutlaka önerilmektedir [6]. Meme koruyucu cerrahi tedavi seçeneklerinin ise etkinliği ile ilgili bir çalışma yoktur [9].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…However, there are several reports of primary squamous cell carcinoma of the breast presenting as breast abscessesGupta et al, (5) Damin et al, (6) Tan et al (7) and Salemis et al (8) reported non-lactating breast abscesses in women aged 39 -70 years, whose primary squamous cell carcinomas of the breast were diagnosed using histologic examination of abscess walls. Primary squamous cell carcinoma of the breast is rare, accounting for less than 0.4% of all cases of breast cancer.…”
Section: Discussionmentioning
confidence: 99%